Committed Actors, Institutional Complexity, and Pathways to Compromise: The Emergence of Islamic Banking in Germany - Ali Aslan Gümüşay; Renate E. Meyer; Markus A. Höllerer (Journal of Management Studies, 2024)
The formation of the first Islamic bank in Germany in 2015 came with considerable tensions at the interface of the religious logic, on the one hand, and the state logic, on the other. With the Islamic religious logic being novel to the German field of banking and finance, innovative templates were established to deal effectively with the resulting tensions and conflicts. Drawing on qualitative data, we investigate how the bank, with its strong commitment to Islam, navigated such novel institutional complexity and the challenges stemming from the jurisdictional overlap. We identify four distinct compromise mechanisms in this institutionally complex situation, in which a committed actor prioritizes one logic over another: explaining, convincing, conceding and suspending. Importantly, as options, these mechanisms are situated in a cascading order of preference for the focal actor. More generally, our research posits that in any encounter between institutional logics in which the specific instantiation of a logic stems from a foreign interinstitutional system, the resulting novel institutional complexity may necessitate the development of innovative templates which, at the same time, may imply `stretching' an institutional logic and, in consequence, impact the compatibility of its jurisdictional claims.
Keywords: 650; commitment; compromise; institutional complexity; institutional logics; interinstitutional system; Islamic banking